Effect of time interval between the second Improvest® dose and slaughter and corn dried distillers grains with solubles feeding strategies on carcass composition, primal cutout, and pork quality of immunologically castrated pigs. (May 2017) - Harris, E.K.; Mellencamp, M.A.; Johnston, L.J.; Cox, R.B.; Shurson, G.C.
Abstract: Effects of dried distillers grains with solubles (DDGS) feeding strategies on carcass composition, primal cutout, and lean quality of immunologically castrated (IC; n = 863) pigs were evaluated, and consisted of: 1) corn-soybean meal (CS) diet (PCon); 2) CS + 40% DDGS (NCon); 3) CS + 40, 30, 20, or 10% DDGS fed in phases 1 to 4, respectively (SD); or 4) CS + 40% DDGS fed in phase 1 to 3 and CS in phase 4 (WD). All pigs received the first dose of Improvest® at 11 weeks. of age, and the second dose was administered at either 9, 7, or 5 weeks. before slaughter at 24 weeks. of age. The SD and WD improved carcass dressing percentage and resulted in intermediate primal cut yields and pork loin quality compared with pigs fed PCon and NCon. Increasing the time interval between second dose of Improvest® and slaughter increased adipose tissue accretion but did not affect lean quality of pork.